2019
DOI: 10.1002/ecs2.2762
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term trajectories of fractional component change in the Northern Great Basin, USA

Abstract: The need to monitor change in sagebrush steppe is urgent due to the increasing impacts of climate change, shifting fire regimes, and management practices on ecosystem health. Remote sensing provides a cost-effective and reliable method for monitoring change through time and attributing changes to drivers. We report an automated method of mapping rangeland fractional component cover over a large portion of the Northern Great Basin, USA, from 1986 to 2016 using a dense Landsat imagery time series. Our method imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 45 publications
4
59
0
Order By: Relevance
“…Component data had a similar pattern whereby shrub and sagebrush cover declined in burned plots; however, cover of herbaceous components did not change (Table 1). validation data sets (Rigge et al 2019), it is unsurprising that we found some discrepancy between our field data and the component data. Given the moderate correspondence observed between the component data and AIM and independent (open black circles, Hist.-Burned), or before 2011 (open gray circles, Hist.-Unburned), and contemporary composition was estimated from data collected from those same plots in 2011-2016 (solid black circles, Cont.-Burned; solid gray circles, Contemp.-Unburned).…”
Section: Fire As a Driver Of Vegetation Changementioning
confidence: 63%
See 4 more Smart Citations
“…Component data had a similar pattern whereby shrub and sagebrush cover declined in burned plots; however, cover of herbaceous components did not change (Table 1). validation data sets (Rigge et al 2019), it is unsurprising that we found some discrepancy between our field data and the component data. Given the moderate correspondence observed between the component data and AIM and independent (open black circles, Hist.-Burned), or before 2011 (open gray circles, Hist.-Unburned), and contemporary composition was estimated from data collected from those same plots in 2011-2016 (solid black circles, Cont.-Burned; solid gray circles, Contemp.-Unburned).…”
Section: Fire As a Driver Of Vegetation Changementioning
confidence: 63%
“…Validation of component cover data at pseudo-invariant pixels, where surface conditions and spectral characteristics are stable over time due to 100% bare ground cover, revealed stable bare ground cover that averaged~94% throughout the time period (Shi et al 2018). Additionally, Rigge et al (2019) reported a moderate relationship between AIM data and component data (average of r 2 of 0.29 across components used in this study; N = 1794), and between component data and independent validation data (average of r 2 of 0.37 across components; N = 156). Additionally, Rigge et al (2019) reported a moderate relationship between AIM data and component data (average of r 2 of 0.29 across components used in this study; N = 1794), and between component data and independent validation data (average of r 2 of 0.37 across components; N = 156).…”
Section: Data Set 2: Landsat-derived Component Datamentioning
confidence: 98%
See 3 more Smart Citations